Peran Bahasa Indonesia sebagai Media Efektif dalam Promosi Kesehatan di Puskesmas Kota Selatan Kota Gorontalo - Dali, Meilina Widya; Ibra Alfareza Thalib; Hasanah, Chelcea Anastasya; Amai, Nayla; Khairunisa, Kayla; Anis, Ririn; Asuke, Maqvira Meilani; Marada, Jamila Nikmatul Rizkah; Malontu, Linda Putri Septianti; Huntua, Nurafni; Paputungan, Juicinta Paramita d; Pido, Fadlun Ul Azmi Utari; Djakaria, Nurul Ais (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Health promotion is a crucial effort in improving public health, and its success is greatly influenced by the communication media used, one of which is language. In addition to aiming to change behavior, health promotion also plays a role in transforming the environment to facilitate changes towards healthier behaviors. Meanwhile, the high use of digital platforms among adolescents makes social media a potential tool with high urgency for disseminating health information. Social media allows fast and widespread access to health education content, improves health literacy, and encourages adolescents' active participation in maintaining their health. Research shows that health promotion through social media is effective in increasing health knowledge and motivating healthy behavior changes. However, its implementation faces various challenges, including the spread of misinformation, lack of content personalization, concerns regarding privacy and security, and adolescents' limited critical thinking skills in selecting accurate information. This paper aims to examine the role of Indonesian in health promotion, both generally and in the context of dissemination through social media for adolescents, as well as its contribution to increasing public understanding, awareness, and behavioral change.